Communication—Deuterium Isotope Separation by Solid Polymer Electrolyte Water Electrolysis. Issue 10 (1st January 2019) - Matsushima, Hisayoshi; Sato, Hanako; Ueda, Mikito; Ito, Hiroshi
Abstract : Electrolytic deuterium (D) separation from protium-containing solution has been investigated. Proton (PEM) and anion exchange membrane (AEM) electrolysis were performed at constant current. The mass analysis of hydrogen gas and water vapor was carried out. For both PEM and AEM electrolysis, the D concentration in the evolved hydrogen gas was lower than that of the initial electrolytic solution. The D concentration in the water vapor was unchanged by PEM electrolysis, but was increased by AEM. The separation factor of PEM was smaller than that of AEM, which was attributed to the humidification state on platinum catalyst.